Sikap guru-guru pelatih terhadap kursus gerak kerja kokurikulum di maktab-maktab perguruan Sarawak - Ravi, A/L Margapandu. (1998)
The purpose of this study was to determine the trainee teachers' attitude toward Co-Curriculum Course in teachers' training colleges in Sarawak. This study was also aimed to find out the significant differences in attitude among trainee teachers' toward Co-Curriculum Course based on selected demographic factors. The study went on further by identifying the relationship between trainee teachers' attitude and the following factors: peer group, lecturers, motivation and past experience and then determined the factors most influencing trainee teachers' attitude toward Co-Curriculum Course.